Synthesis, Crystal Structure, Spectroscopic and Antimicrobial Properties of Ruthenium Complexes of Vinyl Imidazole and 4-Ethylaminomethyl Pyridine Ligands - Moni Kalita, Rinki; Sarma Baruah, Rahul; Medhi, Chitrani (Asian Journal of Chemistry, 2021)
Ruthenium complexes of vinylimidazole (VIMD) and 4-ethylaminomethyl pyridine (EMP) ligands were synthesized and characterized by XRD and spectroscopic methods. The binding of these Ru(IIII) complexes with calf thymus-DNA has been studied by UV-visible spectroscopic and electrochemical studies. A prominent increase in the intensity of fluorescence spectra of these complexes with CT-DNA was observed and a distinct UV-visible spectral shift in presence of CT-DNA is probably due to an interaction of these complexes with CT-DNA. The evidence of DNA binding has been found from the change in the intensity of fluorescence and UV visible spectra. Also, the electron transfer ability of these complexes is very important in order to rationalize their activity towards the biological system therefore, we have studied the electrochemical studies of these complexes by using cyclic voltammetry. From this study, it is possible to draw some ideas on electrochemical potentials of the complexes relevant to biological reduction possibly Ru(III)/Ru(II). Both complexes were also tested for antimicrobial activity against bacterial strain and responses well as antimicrobial agent.